The relationship between prenatal exposure to organophosphate insecticides and neurodevelopmental integrity of infants at 5-weeks of age - Sittiwang, Supattra; Nimmapirat, Pimjuta; Suttiwan, Panrapee; Promduang, Wathoosiri; Chaikittipornlert, Nattapon; Wouldes, Trecia; Prapamontol, Tippawan; Naksen, Warangkana; Promkam, Nattawadee; Pingwong, Sureewan; Breckheimer, Adrian; Cadorett, Valerie; et al. (Frontiers in Epidemiology, 2022)
Introduction Organophosphate (OP) insecticides are among the most abundantly used insecticides worldwide. Thailand ranked third among 15 Asian countries in its use of pesticides per unit hectare and fourth in annual pesticide use. More than 40% of Thai women of childbearing age work on farms where pesticides are applied. Thus, the potential for pregnant women and their fetuses to be exposed to pesticides is significant. This study investigated the relationship between early, mid, and late pregnancy maternal urine concentrations of OP metabolites and infant neural integrity at 5 weeks of age. Method We enrolled women employed on farms from two antenatal clinics in the Chiang Mai province of northern Thailand. We collected urine samples monthly during pregnancy, composited them by early, mid and late pregnancy and analyzed the composited samples for dialkylphosphate (DAP) metabolites of OP insecticides. At 5 weeks after birth, nurses certified in use of the NICU Network Neurobehavioral Scale (NNNS) completed the evaluation of 320 healthy infants. We employed generalized linear regression, logistic and Poisson models to determine the association between NNNS outcomes and DAP concentrations. All analyses were adjusted for confounders and included creatinine as an independent variable. Results We did not observe trimester specific associations between DAP concentrations and NNNS outcomes. Instead, we observed statistically significant inverse associations between NNNS arousal (β = −0.10; CI: −0.17, −0.002; p = 0.0091) and excitability [0.79 (0.68, 0.92; p = 0.0026)] among participants with higher average prenatal DAP concentrations across pregnancy. We identified 3 NNNS profiles by latent profile analysis. Higher prenatal maternal DAP concentrations were associated with higher odds of being classified in a profile indicative of greater self-regulation and attention, but arousal and excitability scores below the 50th percentile relative to US normative samples [OR = 1.47 (CI: 1.05, 2.06; p = 0.03)]. Similar findings are also observed among infants with prenatal exposure to substances of abuse (e.g., methamphetamine). Discussion Overall, the associations between prenatal DAP concentrations and NNNS summary scores were not significant. Further evaluations are warranted to determine the implications of low arousal and excitability for neurodevelopmental outcomes of attention and memory and whether these results are transitory or imply inadequate responsivity to stimulation among children as they develop.